Assessing the Disclosure of Environmental, Social, and Governance on Financial Performance and Firm Value - Agustia, I Komang Edy; Damayanti, Ni Nyoman Sri Rahayu; Sari, A.A Pt Agung Mirah Purnama (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2026)
This study aims to analyze the influence of Environmental, Social, and Governance (ESG), leverage, and firm size on financial performance proxied by Return on Assets (ROA) and firm value proxied by Price to Book Value (PBV) in automotive firms listed on the Indonesia Stock Exchange for the 2022-2024 period. This research uses a quantitative approach with archival data obtained from the firm's annual reports and sustainability reports. The sample was determined using purposive sampling techniques and resulted in 33 observations from 11 firms over three years. All data was processed using EViews 12 software with a panel data regression method through the selection of the best model based on the Chow, Hausman, and Lagrange Multiplier tests. The results of the study show that ESG does not have a significant effect on firm performance and firm value. Meanwhile, the control variable leverage is found to have a negative effect on financial performance and firm value. In contrast, the control variable firm size does not have a significant effect on financial performance, as measured by Return on Assets (ROA), nor on firm value, proxied by Price to Book Value (PBV).